From nurture to deviance: a study on parenting style and juvenile delinquency - Sun, Weihong (Deviant behavior, 2025)
Drawing on data and quantitative analysis from the 2019 Recidivism Survey conducted by the Ministry of Justice in China, this study unveils a significant correlation between parenting styles, parent-child relationships, and juvenile delinquency. Negative parenting practices can lead to increased anxiety or a lack of self-control, especially in scenarios characterized by inadequate parental supervision. This shortfall in self-regulation is directly associated with a surge in criminal behavior among adolescents, thereby elevating the risk of engaging in delinquent activities. Furthermore, poor parent-child relationships exacerbate the adverse effects of insufficient parental oversight on juvenile misconduct. Youths with diminished social and emotional bonds to their parents are more susceptible to diverging from societal norms and participating in delinquent behaviors. Therefore, effective intervention strategies aimed at curbing juvenile delinquency should focus on improving parental supervision and guidance while simultaneously nurturing positive parent-child relationships.